# trigonometry

how do i simplify (secx - cosx) / sinx?

i tried splitting the numerator up so that i had (secx / sinx) - (cosx / sinx)

and then i changed sec x to 1/ cosx so that i had

((1/cosx)/ sinx) - (cos x / sinx)

after that i get stuck

1. 👍 0
2. 👎 0
3. 👁 927
1. sec x = 1 / cos x

sec x - cos x = 1 / cos x - cos x =

1 / cos x - cos ^ 2 x / cos x = ( 1 - cos ^ 2 x ) / cos x

________________________________________

Remark :

1 - cos ^ 2 x = sin ^ 2 x

_______________________________________

1 / cos x - cos ^ 2 x / cos x = ( 1 - cos ^ 2 x ) / cos x = sin ^ 2 x / cos x

( sec x - cos x ) / sin x = ( sin ^ 2 x / cos x ) / sin x =

sin ^ 2 x / ( sin x * cos x ) =

sin x * sin x / ( sin x * cos x ) =

sin x / cos x = tan x

( sec x / sin x ) - ( cos x / sin x ) = tan x

1. 👍 1
2. 👎 0

## Similar Questions

1. ### Pre-calculus

Prove the following identities. 1. 1+cosx/1-cosx = secx + 1/secx -1 2. (tanx + cotx)^2=sec^2x csc^2x 3. cos(x+y) cos(x-y)= cos^2x - sin^2y

2. ### Trig.......

I need to prove that the following is true. Thanks (2tanx /1-tan^x)+(1/2cos^2x-1)= (cosx+sinx)/(cosx - sinx) and thanks ........... check your typing. I tried 30ยบ, the two sides are not equal, they differ by 1 oh , thank you Mr

3. ### math;)

The equation 2sinx+sqrt(3)cotx=sinx is partially solved below. 2sinx+sqrt(3)cotx=sinx sinx(2sinx+sqrt(3)cotx)=sinx(sinx) 2sin^2x+sqrt(3)cosx=sin^2x sin^2x+sqrt(3)cosx=0 Which of the following steps could be included in the

4. ### Trig

Verify the identity: tanx(cos2x) = sin2x - tanx Left Side = (sinx/cosx)(2cos^2 x -1) =sinx(2cos^2 x - 1)/cosx Right Side = 2sinx cosx - sinx/cosx =(2sinxcos^2 x - sinx)/cosx =sinx(2cos^2 x -1)/cosx = L.S. Q.E.D.

1. ### Pre-Calc

How to simplify secx(sinx/tanx)?

2. ### maths

proof that tanx + secx -1/tanx - secx+1 = 1+sinx/cosx

3. ### Calculus

determine the absolute extreme values of the function f(x)=sinx-cosx+6 on the interval 0

4. ### Math

(sinx - cosx)(sinx + cosx) = 2sin^2x -1 I need some tips on trigonometric identities. Why shouldn't I just turn (sinx + cosx) into 1 and would it still have the same identity?

1. ### precal

1/tanx-secx+ 1/tanx+secx=-2tanx so this is what I did: =tanx+secx+tanx-secx =(sinx/cosx)+ (1/cosx)+(sinx/cosx)-(1/cosx) =sinx/cosx+ sinx /cosx= -2tanxI but I know this can't be correct because what I did doesn't end as a

2. ### Trigonometry Check

Simplify #3: [cosx-sin(90-x)sinx]/[cosx-cos(180-x)tanx] = [cosx-(sin90cosx-cos90sinx)sinx]/[cosx-(cos180cosx+sinx180sinx)tanx] = [cosx-((1)cosx-(0)sinx)sinx]/[cosx-((-1)cosx+(0)sinx)tanx] = [cosx-cosxsinx]/[cosx+cosxtanx] =

3. ### Math 12

Simplify #1: cscx(sin^2x+cos^2xtanx)/sinx+cosx = cscx((1)tanx)/sinx+cosx = cscxtanx/sinx+cosx Is the correct answer cscxtanx/sinx+cosx? Simplify #2: sin2x/1+cos2X = ??? I'm stuck on this one. I don't know what I should do.

4. ### Trigonometry

Simplify #1: cscx(sin^2x+cos^2xtanx)/sinx+cosx = cscx((1)tanx)/sinx+cosx = cscxtanx/sinx+cosx Is the correct answer cscxtanx/sinx+cosx? Simplify #2: sin2x/1+cos2X = ??? I'm stuck on this one. I don't know what I should do.